2012
DOI: 10.1007/s10482-012-9791-2
|View full text |Cite
|
Sign up to set email alerts
|

Study in vitro of the impact of endophytic bacteria isolated from Centella asiatica on the disease incidence caused by the hemibiotrophic fungus Colletotrichum higginsianum

Abstract: Thirty-one endophytic bacteria isolated from healthy leaves of Centella asiatica were screened in vitro for their ability to reduce the growth rate and disease incidence of Colletotrichum higginsianum, a causal agent of anthracnose. Isolates of Cohnella sp., Paenibacillus sp. and Pantoea sp. significantly stimulated the growth rate of C. higginsianum MUCL 44942, while isolates of Achromobacter sp., Acinetobacter sp., Microbacterium sp., Klebsiella sp. and Pseudomonas putida had no influence on this plant patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Among 42 endophytic actinomycetes obtained from seven medicinal plants, Streptomyces was the dominant genus ( n = 28, 66.6% of all isolates), a finding consistent with other reports from different hosts showing the dominance of species within the Streptomyces genus (Coombs and Franco, 2003 ; Cao et al, 2004 ). Besides Streptomyces sp., other genera were also reported occasionally from medicinal plants like Microbacterium from Maytenus austroyunnanesis (Qin et al, 2012 ), Leifsonia from Ginseng roots (Qiu et al, 2007 ) and Brevibacterium was isolated from Centella asiatica and Conyza canadensis (Kim et al, 2012 ; Rakotoniriana et al, 2013 ) Therefore, it looks like that these reported rare genera are also able to associate endophytically with various hosts. The Streptomyces genus has an excellent track record for the discovery of secondary metabolites.…”
Section: Discussionmentioning
confidence: 93%
“…Among 42 endophytic actinomycetes obtained from seven medicinal plants, Streptomyces was the dominant genus ( n = 28, 66.6% of all isolates), a finding consistent with other reports from different hosts showing the dominance of species within the Streptomyces genus (Coombs and Franco, 2003 ; Cao et al, 2004 ). Besides Streptomyces sp., other genera were also reported occasionally from medicinal plants like Microbacterium from Maytenus austroyunnanesis (Qin et al, 2012 ), Leifsonia from Ginseng roots (Qiu et al, 2007 ) and Brevibacterium was isolated from Centella asiatica and Conyza canadensis (Kim et al, 2012 ; Rakotoniriana et al, 2013 ) Therefore, it looks like that these reported rare genera are also able to associate endophytically with various hosts. The Streptomyces genus has an excellent track record for the discovery of secondary metabolites.…”
Section: Discussionmentioning
confidence: 93%
“…The total leaf surface area greatly exceeds the terrestrial land area in forest ecosystems. Therefore, plant leaves and needles provide vast habitats for diverse bacteria and fungi, especially foliar endophytic fungi (Saucedo-Garcia et al, 2014 ; Jia et al, 2020 ; Quiring et al, 2020 ; Shahrtash and Brown, 2020 ) and bacteria (Rakotoniriana et al, 2013 ; Yu et al, 2015 ; Carrell et al, 2016 ). Foliar endophytes perform multiple functions (Jia et al, 2020 ) and participate in nutrient uptake (Madhaiyan et al, 2015 ; Moyes et al, 2016 ; Christian et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…B. amyloliquefaciens UCM5113 and its lipopeptide extracts have in vitro antifungal activity against A. brassicicola ( Asari et al, 2017 ). B. subtilis BCA31 and its culture filtrate markedly inhibited in vitro mycelial growth of C. higginsianum ( Rakotoniriana et al, 2013 ). However, no biocontrol has been established on Chinese cabbage plants against the two fungal infections.…”
mentioning
confidence: 99%